HANDBOOKS AGAINST HERESY IN THE WEST, FROM THE LATE FOURTH TO THE LATE SIXTH CENTURIES - Mcclure, Judith (The journal of theological studies, 1979)
JUDITH MCCLURE; HANDBOOKS AGAINST HERESY IN THE WEST, FROM THE LATE FOURTH TO THE LATE SIXTH CENTURIES, The Journal of Theological Studies, Volume XXX, Issue 1,